2011
DOI: 10.1109/led.2011.2121052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EUV Irradiation on Poly-Si SONOS NVM Devices

Abstract: The effects of extreme-ultraviolet (EUV)-irradiationinduced damage on the characteristics of a silicon-oxide-nitrideoxide-silicon (SONOS) memory device are investigated. After EUV irradiation, changes in the memory window and program/ erase speed indicate the generation of positive charges and new traps. Retention performance degrades after high-dose irradiation, which indicates that the tunneling layer is damaged. Endurance performance degrades severely because the damage in the blocking oxide results in seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…EUV irradiation during processing may result in reliability issue. Recently, we have reported the impact of EUV irradiation on a SONOS memory cell and observed that each layer in the ONO stack would be damaged by the EUV irradiation [4].…”
Section: Introductionmentioning
confidence: 99%
“…EUV irradiation during processing may result in reliability issue. Recently, we have reported the impact of EUV irradiation on a SONOS memory cell and observed that each layer in the ONO stack would be damaged by the EUV irradiation [4].…”
Section: Introductionmentioning
confidence: 99%